Sistem Manajemen Perhitungan Bunga Pinjaman dan Penyusunan Laporan Keuangan Koperasi - Eni Endaryati; Jarot Dian Susatyono; Vivi Kumalasari Subroto; Hendri Rasminto; Didik Darmadi (CV. ALIM'SPUBLISHING, 2024)
The use of technology is one solution in helping problems in various circles, both in the world of education and in companies. One of them is the application of an accounting information system to enter, process or report a company's accounting. This application can produce data processing quickly and accurately. This will of course save time and also reduce errors that occur when work is done manually. Like cooperatives, cooperatives must use an accounting information system so that work can be done quickly and accurately. PGRI Kosera's activities in Central Java are in the savings and loans sector. The savings and loan recording process at Kosera PGRI Central Java is not very effective, and because the recording process is repetitive, there is still too much risk of inaccurate and quick misinformation to be reported using Ms. Excel still requires previous data processing from bookkeeping, both deposits, loans and installments, resulting in delays in submitting reports to management. Therefore, in a computerized system that can process membership data, journals, savings transactions, loans and installments, reports made by the Kosera Pgri Cooperative will be valid in programming languages, especially in calculating installment interest costs and financial reports. From the results of the program created, data entry errors and interest calculation errors can be reduced, financial reports can be produced more quickly, and effective and efficient achievements can be achieved.